Stroškovna ocena delovanja stalne arbitraže pri Zavarovalnici Triglav, d.d. - Eigner, Matej (LeXonomica, 2009)
Cost analysis of Triglav Insurance Company's Institutional Arbitration. This paper presents the results of a statistical analysis of Triglav Insurance Company’s Institutional Arbitration. The main stress is on cost evaluation of arbitration proceedings. This evaluation represents one of the most important motivation factors in a process of decision-making about the most appropriate method of dispute resolution. With application of economics and statistical data this paper presents a position and role of the insurance arbitration in relation to other forms of alternative dispute resolution and national courts.Povzetek. Prispevek predstavlja izsledke statistične analize delovanja stalne arbitraže pri Zavarovalnici Triglav, d.d., pri čemer je posebna pozornost namenjena stroškovni oceni arbitražnega postopka. Navsezadnje je ravno stroškovna učinkovitost eden pomembnejših motivacijskih dejavnikov pri izbiri ustreznega načina reševanja spora. Z uporabo ekonomsko - statističnih kazalnikov je orisan položaj in vloga zavarovalniške arbitraže v odnosu do ostalih oblik alternativnega reševanja sporov ter nacionalnih sodišč.
Keywords: arbitration law; institutional arbitration; Triglav Insurance Company; cost efficinecy; statistical analysis; arbitration rules